Questioning scrutiny: the effect of Prime Minister's Questions on citizen efficacy and trust in parliament. Issue 2 (3rd April 2021) - Convery, Alan; Haines, Pavielle; Mitchell, James; Parker, David C. W.
ABSTRACT: In most democratic regimes, the public often dislikes and distrusts parliamentarians. This should not surprise: the public likes neither compromise nor conflict, both of which are legislative hallmarks. One of the most famous examples of parliamentary conflict is Prime Minister's Questions (PMQs) in the British House of Commons. It is the most viewed and commented upon part of the parliamentary week, but attracts strong criticism as a noisy charade promoting a poor image of politics. Does PMQs undermine individual levels of political efficacy and trust in Parliament, as some commentators suggest? We use an experimental design to answer this question and find evidence to suggest that, contrary to its negative reputation, PMQs does not adversely affect most citizens' perceptions.